PEMILIHAN LAPTOP TERBAIK MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - Nia Nuraeni Nuraeni; Muhammad Reyhan Firdaus (Lembaga Penelitian dan Pengabdian Masyarakat - Universitas Teknologi Digital Indonesia, 2022)
Laptops are tools of technological advancement that are beneficial to society. This has resulted in the emergence of various types of laptop brands with different specifications. However, there are still many consumers who do not understand laptop specifications. Therefore, a study was made to determine decisions in choosing the best laptop using the Simple Additive Weighting (SAW) method to assist in the calculations, in order to get recommendations for choosing the best laptop. The Simple Additive Weighting (SAW) method can be regarded as a method with weighted calculations or additions. The results of the calculation of several criteria using the SAW method get the highest preference value from the criteria, the first order is the MSI SUMMIT E14 EVO = 27.85, the second order is the Asus Vivobook Pro 14 K3400PH = 26.78 brand and the HP (Hawlett Packard) 250 G8 = 26.78, in third place is the Lenovo Ideapad Slim 3 14 = 26.53 and HP (Hawlett Packard) Pavilion X360 DY0063TU = 26.53. Thus it can be concluded that the Simple Additive Weighting method is considered relevant in solving the problem of selecting the best laptop